Ways to transform management of competitiveness at Ukrainian enterprises under conditions of the russian military aggression - Khatser, Maxim; Bulhakova, Katerina (Management and Entrepreneurship: Trends of Development, 2022)
The article is dedicated to forming new scientific solutions for improving the competitiveness management of economic entities in Ukraine under the impact of changes in the external and internal environment caused by military actions on the country's territory. It has been proven that Ukrainian enterprises need to make significant changes in the management of competitiveness to ensure the appropriate level of resistance to competitors in the domestic and foreign markets to sell products (works, services). The purpose of the article is to form a set of ways to transform the management of competitiveness at Ukrainian enterprises under conditions of Russian military aggression, taking into account the presence of negative and positive internal and external factors of influence on large, medium, small and micro domestic enterprises. Methodology: a set of general and special methods was used at the empirical and theoretical levels, namely: the abstraction method for selecting groups of enterprises for conducting research; methods of analysis and synthesis to identify critical external and internal factors of positive and negative impact on the management of competitiveness of Ukrainian enterprises; comparison to determine the features of competitiveness management at enterprises of different groups in the country (large, medium, small, micro); methods of systematization, grouping and logical generalization for systematization of information, conclusion formation and statement of scientific proposals of the article. The work implements system-functional, historical, and systemic approaches in revealing and solving the problems of competitiveness management at Ukrainian enterprises in the conditions of Russian military aggression. Results: a set of ways to transform the management of competitiveness of Ukrainian business entities under conditions of Russian military aggression, taking into account the division of enterprises into large, medium, small, and micro enterprises, has been developed, which enables domestic business entities to win the competition on domestic and foreign product sales markets (works, services).JEL Classification: D21, М21.